EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN DURIAN (DURIO ZIBETHINUS) DI KOTA SAWAHLUNTO - Rachmawati, Fena; Syarief, Azhari (JURNAL BUANA, 2025)
This research aims to determine the suitability of land for durian plants in Sawahlunto City. 2) Productivity of durian plants in Sawahlunto City This research is a type of quantitative descriptive research using the overlay method between soil type maps, slope maps, geological maps, landform maps, and land use maps obtained from related agencies, which are then matched. Data collection techniques include field observations, interviews, and laboratory analysis. The results of this research: 1) The land suitability class for durian plants in the city of Sawahlunto is divided into two classes, namely the very suitable class (S1) with an area of 21311 ha, or 87.56%, and the quite suitable class (S2) with an area of 3028 ha, or 12.4%. 2) Durian productivity on very suitable land (S1) is 3.05 tons/ha/year, while low durian productivity on quite suitable land (S2) is 2.3 tons/ha/year. 3) The results of the interview contained several points, namely the size of the farmer's land, the price of durian fruit, and pests that attack durian plants.